Leukogram Profile and Clinical Status in vivax and falciparum Malaria Patients from Colombia - Alberto Tobón-Castaño; Esteban Mesa-Echeverry; Andrés Felipe Miranda-Arboleda (Journal of Tropical Medicine)
Introduction. Hematological alterations are frequent in malaria patients; the relationship between alterations in white blood cell counts and clinical status in malaria is not well understood. In Colombia, with low endemicity and unstable transmission for malaria, with malaria vivax predominance, the hematologic profile in malaria patients is not well characterized. The aim of this study was to characterize the leukogram in malaria patients and to analyze its alterations in relation to the clinical status. Methods. 888 leukogram profiles of malaria patients from different Colombian regions were studied: 556 with P. falciparum infection (62.6%), 313 with P. vivax infection (35.2%), and 19 with mixed infection by these species (2.1%). Results. Leukocyte counts at diagnosis were within normal range in 79% of patients and 18% had leucopenia; the most frequent alteration was lymphopenia (54%) followed by monocytosis (11%); the differential granulocyte count in 298 patients revealed eosinophilia (15%) and high basophil counts (8%). Leukocytosis, eosinopenia, and neutrophilia were associated with clinical complications. The utility of changes in leukocyte counts as markers of severity should be explored in depth. A better understanding of these hematological parameters will allow their use in prompt diagnosis of malaria complications and monitoring treatment response.